The helsinki affair ebook - Pitoniak, Anna (2023)
One of The Washington Post 's Best Thrillers of 2023 It's the case of Amanda's lifetime but solving it will require her to betray another spy—who just so happens to be her father in this "delicious spy novel" ( People ). Spying is the family business. Amanda Cole is a brilliant young CIA officer following in the footsteps of her father, who was a spy during the Cold War. It takes grit to succeed in this male-dominated world—but one hot summer day, when a Russian defector walks into her post, Amanda is given the ultimate chance to prove herself. The defector warns of the imminent assassination of a US senator. Though Amanda takes the warning seriously, her superiors don't. Twenty-four hours later, the senator is dead. And the assassination is just beginning. Corporate blackmail, covert manipulation, corrupt oligarchs: the Kremlin has found a dangerous new way to wage war. Teaming up with Kath Frost, a fearless older woman and legendary spy, Amanda races from Rome to London, from St. Petersburg to Helsinki, unraveling the international conspiracy. But as she gets closer to the truth, a central question haunts her: Why was her father's name written down in the senator's notes? What does Charlie Cole really know about the Kremlin plot? The Helsinki Affair is an "propulsive, captivating spy novel," ( Good Morning America )—but this time with a refreshing female-centric twist. Perfect for fans of John le Carré and Daniel Silva, this book introduces Pitoniak as a singular new talent in the world of spy fiction.